Modulation of iron metabolism in aging and in Alzheimer's disease: relevance of the choroid plexus - Mesquita, Sandro D.; Ferreira, Ana C.; Sousa, Joao C.; Santos, Nadine C.; Correia-Neves, Margarida; Sousa, Nuno; Palha, Joana A.; Marques, Fernanda (Frontiers in Cellular Neuroscience, 2012)
Iron is essential for mammalian cellular homeostasis. However, in excess, it promotes free radical formation and is associated with aging-related progressive deterioration and with neurodegenerative disorders such as Alzheimer’s disease (AD). There are no mechanisms to excrete iron, which makes iron homeostasis a very tightly regulated process at the level of the intestinal absorption. Iron is believed to reach the brain through receptor mediated endocytosis of iron-bound transferrin by the brain barriers, the blood-cerebrospinal (CSF) fluid barrier, formed by the choroid plexus (CP) epithelial cells and the blood-brain barrier formed by the endothelial cells of the brain capillaries. Importantly, the CP epithelial cells are responsible for producing most of the CSF, the fluid that fills the brain ventricles and the subarachnoid space. Recently, the finding that the CP epithelial cells display all the machinery to locally control iron delivery into the CSF may suggest that the general and progressive senescence of the CP may be at the basis of the impairment of regional iron metabolism, iron-mediated toxicity and the increase in inflammation and oxidative stress that occurs with aging and, particularly, in AD.